STUDENTS' PERCEPTIONS OF USING SONG LYRICS AS A MEDIA TO IMPROVE VOCABULARY MASTERY - Sri Dilago; Nihta Liando; Fridolin Kukus (Program Studi Pendidikan Bahasa Inggris, 2022)
Song is one of the teaching media that can be used to develop English language skills. Using songs in the classroom brings many benefits to the classroom. The purpose of this study is to investigate how students’ perceive the use of lyrics as a media to improve vocabulary mastery at SMP Negeri 4 Halmahera Barat. This research used a quantitative descriptive method. The subject of this research consisted of 30 students at the 8th grade of SMP Negeri 4 Halmahera .To collect the data, this research used a 20 item questionnaire given to 30 students. The result of the study shows that most students agree to use song lyrics as a media to improve vocabulary mastery. This could be seen in the responses of the respondents. The score of student's questionnaire there are 4 responses choose strongly agree, 20 responses choose agree, 2 responses choose disagree, and the last 1 responses choose strongly disagree. The highest score was 92 and the lowest score was 37. From the analysis of the scores of students is 2161, the mean score is 72.03% and the interval score is between 68% - 83%. It concluded that the majority of students agree that song lyrics could improve students’ vocabulary mastery